Humanistic nursing and nursing ethics of infection and infectious diseases (传染与感染性疾病人文护理及护理伦理) - TIAN Yiying (田艺莹); LI Jiayue (李佳玥); ZHANG Bei (张北); QI Shasha (齐莎莎); GAO Xiaoming (高晓明); REN Yuanyuan (任媛媛); JIANG Mingyue (姜明月) (Association of Integrative Nursing, 2023)
Nurses should pay more attention to nursing of patients with infections and infectious diseases, and carry out effective hygiene management and infection care to minimize the infection rate of infectious disease pathogens. This article briefly analyzed the ethical issues of infection and infectious disease care, and explored specific nursing methods for infection and infectious diseases, aiming to provide assistance and reference for modern infection and infectious disease care in China. (在面对传染与感染性疾病患者时, 护理人员需要高度重视, 开展有效的卫生管理和感染护理, 最大限度地降低传染与感染性疾病病原体的感染风险。本文针对传染与感染性疾病护理的伦理问题进行简要分析, 并探讨传染与感染性疾病的具体护理方式, 旨在为临床传染与感染性疾病护理工作提供帮助与参考。)